Fuzzy databases : modeling, design, and implementation - Galindo, Jose, 1970-; Urrutia, Angelica; Piattini, Mario, 1966- (Hershey [Pa.] : Idea Group Pub., 2006)
'This book includes an introduction to fuzzy logic, fuzzy databases and an overview of the state of the art in fuzzy modeling in databases' -- Provided by publisher
Includes bibliographical references (p. 282-298) and index
Keywords: Database management; Fuzzy sets